Photoinactivation of Latent Herpes Simplex Virus in Rabbit Kidney Cells - Kelleher, J. J. (1976)
The photoinactivation of actively and nonactively growing herpes simplex virus by neutral red and proflavine was studied in rabbit kidney cells. Active virus growth was inhibited by both dyes under conditions which did not destroy the cells. Neutral red caused a much greater inhibition than proflavine. Neutral red also caused a reduction in the reactivation rate of latent virus when the infected cells were treated during the latent period. In the treated cultures that did reactivate virus, the average length of the latent period was increased over the control value. Proflavine treatment did not reduce the rate of reactivation of latent virus and did not increase the average latent period of the treated cultures.